Ocular outcomes of the sodium-glucose cotransport inhibitors: A systematic review of cohort studies - Nathaniel Eraikhuemen; Bria George; Simon Leung; Shalonda Barnes Warren; Valerie Marcellus; Delany Santos Ferrer; Quovadis Epps (Journal of Clinical Ophthalmology and Research)
Importance: Emerging data have shown that sodium-glucose cotransporter inhibitors (SGLTi) improve cardiovascular (CV) and renal outcomes in patients with or without diabetes mellitus type II (DM II). Although post hoc subgroup analyses from CV and renal outcome trials have reported data on the effects of these agents on the eyes, data regarding ocular effects as the primary outcome are limited. Objective: In this systematic review, we sought to explore the ocular events of SGLTi reported as a primary outcome in patients with or without DM II. Diabetic retinopathy (DR), diabetic macular edema (DME), glaucoma, dry eye disease (DED), and retinal vein occlusion (RVO) were the ocular outcomes reviewed. Evidence Review: The review was performed and reported according to the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A systematic search of the scientific literature databases in PubMed, Cochrane, Google Scholar, Medline, and EMBASE from March 2013, when the first SGLT2i was approved, through July 31, 2024, was performed. Cohort studies that directly assessed ocular events as a primary outcome in patients taking SGLTi were included. Findings: After a thorough literature search, seven cohort studies of patients with diabetes under management with SGLTi met our inclusion criteria and were used to conduct the review with a combined total of 366,917 participants. In most of the studies, ocular outcomes of SGLTi were compared with other glucose lowering drugs, including pioglitazones, glucagon-like peptide-1 agonists, sulfonylureas, or dipeptidyl peptidase IV inhibitors. The data of our study reflect a reduced risk of glaucoma, DED, and DME in patients with diabetes, although the overall effect on DR and RVO remain inconclusive. Conclusion and Relevance: As SGLTi continue to show promise outside of merely glycemic control, we challenge the scientific community to explore more of its potential benefits within ophthalmology. Our findings also show a need for more studies that specifically assess the effect of SGLT2i on ocular outcomes.